SERI Methods to Measure the Vulnerability of Shallot Farming to Climate Change in Tapin Regency, South Kalimantan - Hasanah, Lisda Noorizatil; Fatah, Luthfi; Bachri, Ahmad Alim; Susanti, Hilda (Technium Sustainability, 2023)
This study analyses the vulnerability of shallot farming to climate change in Tapin Regency, South Kalimantan. Data collection methods in this study consisted of questionnaires, in-depth interviews, observations, documentation, and a literature review. The SERI (shock–exposure–response–impact) analysis method was used to analyse the vulnerability of shallot farming to climate change in Tapin Regency. The results showed that climate change is the main shock to shallot farming in Tapin Regency. Extreme weather, namely, extreme rainfall events, causes water to become stagnant (flood) so that roots and fruit rot. These exposures extensively decreased the shallot harvest (harvest failure) and decreased the sale price of shallots (loss), and most farmers did not plant shallots again. Shallot farmers responded to the shocks that occurred by not planting shallots; however, some farmers focused extra attention on farming practices, but almost all farmers switched to planting other commodity crops. The impact of these shocks on farmers were decreases/losses in income and increases in costs. Buffer capacities that can be implemented to reduce the impact of these impacts are (1) using healthy and clean superior varieties that are resistant to extreme weather events and pest invasions; (2) setting cropping schedules and cropping patterns; and (3) increasing the capacity of farmers through education and training, especially in terms of how to conduct shallot farming during extreme weather events and how to properly control plant pests and diseases.